Do Socio-economic Conditions and Personal Behaviour Influence the Adoption of Climate Change Mitigating Measures - Meena, Dinesh Chand; Kumari, Maina; Kishore, Prabhat; Bangararaju T, S. V.; Bishnoi, Rajesh (Indian Journal of Extension Education, 2023)
This study aimed to identify the factors affecting farmers’ perception of climate change and the adoption of Soil and Water Conservation (SWC) measures as a mitigation strategy for climate change. From the existing literature review, the study has identified the factors that potentially influence the adoption of climate mitigation and adaptation technologies. The binary logit model was employed using survey data collected from the Agra district of Uttar Pradesh during the year 2018-19. Results show that about 60 per cent of households had a clear perception of climate change, and age, education, membership of groups, mass media exposure, and extension agency contacts were key influencing factors in farmers’ perception of climate change. Similarly, education, occupation, mass media exposure, awareness of climate change consequences, climate change perception, and attitude of farmers increase the probability of adopting soil and water conservation measures by the farmers in their fields. Therefore, the study results have significant implications for policies and campaigns promoting adopting climate-smart technologies to make the agricultural system more resilient to climate change.
Keywords: Adoption; Climate change perception; Determinants; Logit; Soil and water conservation